CRIMINALIZATION OF COHABITATION UNDER INDONESIA’S 2023 CRIMINAL CODE: A COST-BENEFIT ANALYSIS PERSPECTIVE - Ridha Islamika; La Syarifuddin; Orin Gusta Andini (Jurnal Ilmiah Advokasi, 2026)
Cohabitation, defined as unmarried couples living together, has recently been criminalized under Article 412 of Indonesia’s 2023 Criminal Code. This policy reflects the state’s intention to regulate moral conduct and protect social values within society. However, the criminalization of private conduct raises important questions regarding its effectiveness and efficiency, particularly when assessed through a law and economics perspective. This study aims to analyze the criminalization of cohabitation under the 2023 Criminal Code using a cost-benefit analysis framework and to examine its legal consequences within the broader legal system. The research employs a doctrinal legal method, supported by a conceptual approach grounded in law and economics theory. The findings indicate that, from a cost-benefit perspective, the criminalization of cohabitation offers potential benefits, including the protection of social norms, moral values, and the institution of family, as well as the prevention of related social problems. However, these benefits are accompanied by significant costs, such as increased burdens on the criminal justice system, higher state expenditures, and potential socio-economic repercussions. Furthermore, as an absolute complaint offense, the enforcement of Article 412 depends on reports from specific parties, which may limit its practical effectiveness. At the systemic level, this provision also risks creating legal disharmony with existing regulations, including marriage and child protection laws. In conclusion, the criminalization of cohabitation in Indonesia’s 2023 Criminal Code reflects a normative commitment to moral regulation but raises concerns regarding its efficiency and coherence within the broader legal framework.Keywords: Cost-Benefit Analysis; Cohabitation; Criminalization; Law and Economics; Indonesian Criminal Code